A Monitoring System for Chronic Diseases— Determining the Parameters Involved - Chen, Rina (Methods of Information in Medicine, 1983)
A procedure for determining the parameters required for implementing a recently suggested monitoring system is described. A table of these parameters is also presented. While the parameters originally suggested were determined so as to increase the efficiency of a single analysis, the parameters presented here are aimed at the early detection of slightly increased rates of occurrences within a number of analyses.
Keywords: Monitoring System; Subtle Epidemics